IMPLEMENTASI PROGRAM BIMBINGAN DAN KONSELING DI SMK LABOR BINAAN FKIP UNRI - Devi, Ayu Puspa; Yakub, Elni; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the types and contents of guidance and counseling programs and find out implementation. The subjects of the study are BK teacher and 25% of the students receivinging the services. The method used in this research is descriptive qualitative. The data were obtained through questionnaire and documentation. The results show that counseling teachers a) applied 17 plus patterns, the planned programs are orientation services, information services, placement and distribution services, content mastery services, individual counseling services, group counseling services, group counseling services, consulting services, mediation services, instrumentation applications, data sets, case conferences, display libraries, home visits, and hand over cases. The unplanned services are advocacy services and unplanned guidance areas are family guidance and religious guidance. b) Implement the program Guidance and counseling services in vocational schools are categorized well. The most frequently implemented services are individual counseling services> 20 times and information services 10-15 times, support services activities that have never been implemented is hand over the case because based on the case book, there is no student problem that needs to be followed up by hand-transfer case. Supporting factors for counseling and counseling services are individual counseling rooms, counselor rooms, meeting rooms, administration rooms, storage rooms, data storage rooms and skateholders also participate. Inhibiting factors in group counseling and group guidance are inadequate counseling rooms. c) the results of students receiving counseling and guidance services need to be included in the class of materials, there is a change that the students feel after consulting with teachers of Guidance and counseling. Keywords: Guidance and Counseling,Implementation, Program